2011
DOI: 10.1128/iai.01180-10
|View full text |Cite
|
Sign up to set email alerts
|

The Staphylococcus aureus KdpDE Two-Component System Couples Extracellular K + Sensing and Agr Signaling to Infection Programming

Abstract: The Kdp system is widely distributed among bacteria. In Escherichia coli, the Kdp-ATPase is a high-affinity K ؉ uptake system and its expression is activated by the KdpDE two-component system in response to K ؉ limitation or salt stress. However, information about the role of this system in many bacteria still remains obscure. Here we demonstrate that KdpFABC in Staphylococcus aureus is not a major K ؉ transporter and that the main function of KdpDE is not associated with K ؉ transport but that instead it regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
99
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(104 citation statements)
references
References 55 publications
3
99
0
2
Order By: Relevance
“…This ATP-dependent potassium uptake system has been best characterized in E. coli and consists of four membrane components KdpABCF and the twocomponent system KdpDE, which is required for KdpABCF expression at a very low potassium concentration when the other uptake systems are no longer sufficient to allow the cell to acquire the necessary amount of ion (31). However, a recent study on the S. aureus KdpDE system suggested that this two-component system has a different function in this organism (32). The S. aureus KdpDE two-component system, which still responds to the extracellular potassium concentration, was found to be no longer required for bacterial survival under low potassium conditions, but instead to control the expression of several well-characterized S. aureus virulence factors (32).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This ATP-dependent potassium uptake system has been best characterized in E. coli and consists of four membrane components KdpABCF and the twocomponent system KdpDE, which is required for KdpABCF expression at a very low potassium concentration when the other uptake systems are no longer sufficient to allow the cell to acquire the necessary amount of ion (31). However, a recent study on the S. aureus KdpDE system suggested that this two-component system has a different function in this organism (32). The S. aureus KdpDE two-component system, which still responds to the extracellular potassium concentration, was found to be no longer required for bacterial survival under low potassium conditions, but instead to control the expression of several well-characterized S. aureus virulence factors (32).…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study on the S. aureus KdpDE system suggested that this two-component system has a different function in this organism (32). The S. aureus KdpDE two-component system, which still responds to the extracellular potassium concentration, was found to be no longer required for bacterial survival under low potassium conditions, but instead to control the expression of several well-characterized S. aureus virulence factors (32). However, additional work is needed to fully understand the function of this two-component system in S. aureus and other Gram-positive bacteria and on the basis of this study its interplay with cellular c-di-AMP levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some bacteria, extracellular K ϩ can act as a signal cation to activate virulence mechanisms (50)(51)(52). In S. mutans Ingbritt, the addition of K ϩ increased the rate of acid production, which is an essential virulence factor (14).…”
Section: Discussionmentioning
confidence: 99%
“…We identified the SCCmec type V element, which is different from that of ST772. Two virulence determinants, a kdp operon (virulence regulator during pathogenesis) and an arginine deiminase locus comprising arcC, arcD, arcB, arcA, and argR genes, not detected by microarray, were found in the genome sequence and later validated by PCR (8).…”
mentioning
confidence: 99%